Case Study 2 - Porto Alegre, Brazil : Participatory Approaches in Budgeting and Public Expenditure Management - World Bank (Washington, DC, 2012)
Run by dictators for over 20 years (1964-1985), Brazil only had a democratic constitution promulgated in 1998 that allowed an already active civil society to function more freely. A country of 156 million, Brazil has been dubbed one of the most unequal, with one of the largest numbers of poor people among comparable middle-income countries. After the end of dictatorship in 1998, people who had earlier opposed dictatorships formed the Workers Party (PT) to seriously take up the agenda of deepening democracy through "popular administration" of government. Having won several municipal elections in 1989, including Sao Paolo with over 10 million people, the PT began a creative experiment of engaging a wide spectrum of people to formulate city budgets. The Porto Alegre case has, in particular, having been nominated by the 1996 UN Summit on Human Settlements in Istanbul as an exemplary 'urban innovation', stood out for demonstrating an efficient practice of democratic resource management. The largest industrial city in Rio Grande do Sul with 1.3 million inhabitants, Porto Alegre has a local economy worth over US$ 7 billion, and for long has had a reputation for hosting a progressive civil society led by intellectuals and labor unions experienced in mobilizing people to partake in public life, including opposing authoritarianism.